The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1007/bf00558228
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urinary excretion kinetics of oral baclofen in healthy subjects

Abstract: Baclofen, a centrally acting muscle relaxant, is used in the treatment of spasticity. Its pharmacokinetics has been derived from plasma and urine data in four healthy subjects, whose renal function was simultaneously measured. After oral administration of a single 40 mg dose, baclofen was mainly excreted unchanged by the kidney, 69 (14)%. The half-life, calculated from extended least squares modelling (ELSMOS) both of plasma and urine data was 6.80 (0.68) h, which is longer than reported in most studies based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 12 publications
4
65
3
2
Order By: Relevance
“…Chodorowski et. al detected 12/18 patients (66%) admitted to the clinic in deep coma, 10/18 patients (55.5%) with acute respiratory failure and cardiac abnormalities including bradycardia (44.4%), hypertension (33.0%) and hypotension (5.5%) in toxication [1]. Baclofen is rapidly and extensively absorbed and eliminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chodorowski et. al detected 12/18 patients (66%) admitted to the clinic in deep coma, 10/18 patients (55.5%) with acute respiratory failure and cardiac abnormalities including bradycardia (44.4%), hypertension (33.0%) and hypotension (5.5%) in toxication [1]. Baclofen is rapidly and extensively absorbed and eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Baclofen is eliminated predominantly by the kidneys and patients with impaired renal function have particular risk for baclofen accumulation [1]. Some authors have suggested that haemodialysis is effective in the removal of baclofen, however the pharmakokinetics of baclofen elimination during haemodialysis remains unclear [2].…”
Section: Introductionmentioning
confidence: 99%
“…Baklofenin büyük bir kısmı böbreklerden elimine olmaktadır (4). Son dönem böbrek yetersizliği olan hastalarda baklofen birikimi olduğu ve yarılanma ömrünün uzadığı belirtilmektedir (19). Yapılan birçok çalışmada renal yetersizliği olan ciddi baklofen toksisite olgularında hemodiyaliz uygulamaları ile serum baklofen kosantrasyonun hızla düştüğü, baklofen yarılanma ömrünün kısaldığı ve klinik semptomların hızla iyileştiği gösterilmiştir (20)(21)(22)(23)(24).…”
Section: Discussionunclassified
“…The slow speed of injection reduced the initial distribution of baclofen along the spinal canal [12]. Biotransformation of baclofen is low and the drug is predominantly excreted unchanged by the kidneys [13].…”
Section: Discussionmentioning
confidence: 99%